The impact of expanded public works programme on job creation on the community of Rambuda in Mutale Municipality, Limpopo Province - Nesengani, Thinandavha J. (University of Limpopo (Turfloop Campus), 2007)
The study was intended to investigate the impact of EPWP in job creation in the Rambuda area in the Mutale municipality of the Vhembe District in the Limpopo Province. Qualitative methods, which involved focus groups interviews and in-depth individual interviews were used to find out the impact of EPWP in job creation. Rambuda area was selected because the project was implemented in that area. The results revealed that the Rambuda EPWP had created many jobs for a number of jobless people including, males, females and youths. The employees were paid on a task base where they were paid R30.00 per task. The implication of the results was that Rambuda EPWP has had a significant impact in terms of job creation in the area.
Thesis (M.Dev.) --University of Limpopo, 2008
Keywords: Expanded Public Works Programme; Job creation; 354.92768; Public works; Job creation -- South Africa